ANALYSIS OF MISCONCEPTIONS IN CHEMISTRY LEARNING: LITERATURE REVIEW - Candra Prasetyo; Lina Fauziyah; Ardinal Efendi (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2023)
This research aims to analyze research trends regarding misconceptions in chemistry majors. This research containsan analytical study of the number of articles published in the last ten years, 2014-2024. This research was carried out by taking 17 SINTA-accredited articles from SINTA 2-5 and International Journal. This research method uses literature riview carried out through the identification and analysis of journals. We found National and International journals published in 2014-2024. The analysis step begins with reading the abstract and data reduction and drawing data conclusions based on the research instruments used. Research topics include the number of publications, type of research, chemical material studied, research subjects, and data analysis techniques. The primary research is qualitative, and the dominant material is acid-base material. Based on the results of this research, several recommendations can serve as guidelines for further research to produce research results that are more useful and have an impact on the lives of Indonesian people, especially in terms of teaching and learning.